Smart Waste Management System Using Lora Technology - Azmi Aina Zafira; Mohd Sahar Norsuzlin; Islam Muhammad Tariqul (E3S Web of Conferences)
In residential areas and commercial spaces, garbage houses serve as important disposal sites. However, rapid urbanization has led to a surge in population, increasing waste production. The conventional waste collection schedules have proven to be inefficient: frequent visits to empty bins are waste resources, while delayed cleaning of overflowing bins harms the environment. To address this challenge, proposals to integrate IoT into smart waste management systems by using LoRa communication for realtime monitoring of fill levels bin and indoor air quality emerge. It involves the integration of sensor technology, IoT connectivity, data analytics, and LoRa technology, leading to more efficient, data-driven, and technologically advanced waste management practices. This digitalization aims to increase operational efficiency, reduce costs, minimize environmental impact, and optimize resource allocation in waste collection and processing.